2018
DOI: 10.3390/f9110725
|View full text |Cite
|
Sign up to set email alerts
|

REDD+ as a Public Policy Dilemma: Understanding Conflict and Cooperation in the Design of Conservation Incentives

Abstract: Command-and-control policies are often criticized as insufficient to tackle tropical deforestation. Over the past two decades, both academics and policy-makers have promoted incentive-based policies, notably REDD+ (Reduced Emissions from Deforestation and forest Degradation), as attractive alternatives to curb forest loss, while also potentially contributing to the poverty reduction of forest-dwelling populations. Governments have been the driving force behind the largest incentive-based forest conservation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Political factors often appeared together in the literature, together with institutional factors. Poor leadership often resulted in poor coordination between vertically and horizontally, unclear authority, weak enforcement, lack of policy consistency, and overlapping or misaligned regulations (Korhonen-Kurki et al 2016, Rosa Da Conceição et al 2018, Chia et al 2019. Implementation was also limited with NCS activities where not a priority for those in power, where decisions were made with short-term objectives in mind, or those in power did not have the technical expertise needed to participate fully in the REDD+ process, but continued to do so for political reasons.…”
Section: Summary and Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Political factors often appeared together in the literature, together with institutional factors. Poor leadership often resulted in poor coordination between vertically and horizontally, unclear authority, weak enforcement, lack of policy consistency, and overlapping or misaligned regulations (Korhonen-Kurki et al 2016, Rosa Da Conceição et al 2018, Chia et al 2019. Implementation was also limited with NCS activities where not a priority for those in power, where decisions were made with short-term objectives in mind, or those in power did not have the technical expertise needed to participate fully in the REDD+ process, but continued to do so for political reasons.…”
Section: Summary and Insightsmentioning
confidence: 99%
“…Good MRV was contingent on available resources, such as technological or labor capacities. Communitybased monitoring approaches also were used to build participation and ownership for projects among IPLCs (Newton et al 2015, Rosa Da Conceição et al 2018. Land-use planning-mapping, identification of land-use drivers, and assessment of ecological conditions-came up almost as often as MRV (n = 39).…”
Section: Technicalmentioning
confidence: 99%
“…In order to prevent REDD+ for becoming 'just another development project' [49] -or as other critics have suggested a 'conservation fad' [82,83] -the advancement of local multisector bottom-up action is necessary to establish foundational coordination, mobilize funding and political will, and encourage collaboration. Achieving this would provide a template for more complex development issues.…”
Section: Perspectives On Redd+mentioning
confidence: 99%
“…Correa et al [32] attribute the apparent lack of effectiveness to the distribution mechanism of the Brazilian Amazon fund that prioritized diverse organizations rather than a strategic selection of projects due to its predetermined theory of change. Rosa da Conceição et al [42] looked at REDD+ in Ecuador and Peru and the pathways of two government-led, incentive-based forest conservation and poverty reduction programs for forest-based populations. They found that political interests affected policy design, resulting in trade-offs for longer-term societal efficiency in favor of short-term administrative goals.…”
Section: Policy Outputs Outcomes and Impactsmentioning
confidence: 99%